PENGARUH GENDER, PENGALAMAN AUDITOR, KOMPLEKSITAS TUGAS, TEKANAN KETAATAN, KEMAMPUAN KERJA DAN PENGETAHUAN AUDITOR TERHADAP AUDIT JUDGEMENT - Reni Yendrawati; Dheane Kurnia Mukti (UII, 2015)
This research was aimed to examine and to obtain empirical evidents on effects of gender, auditor experience, task complexity, obedience pressure, ability and knowledge toward audit judgement taken by auditor. This research was carried out at the DIY BPK representative. Collecting data was conducted by questionare distributed as much 40, however only 35 questionaires replayed, that gender didn’t significanly affect audit judgement, experience, task complexity, ability and knowledge significanly positive affect audit judgement, and obidience pressure significanly negaative effect audit judgement. Keywords: gender, auditor’s experience, task complexity, obidience pressure, ability, knowledge, audit judgement.